Identifying adeno‐associated virus (AAV) vectors that efficiently target high grade glioma cells, for in vitro monitoring of temporal cell responses - Farhana A. Sarker; Yuyan Chen; Adrian Westhaus; Leszek Lisowski; Geraldine M. O'Neill (FEBS Open Bio, 2024)
To improve the translation of preclinical cancer research data to successful clinical effect, there is an increasing focus on the use of primary patient‐derived cancer cells with limited growth in culture to reduce genetic and phenotype drift. However, these primary lines are less amenable to standardly used methods of exogenous DNA introduction. Adeno‐associated viral (AAV) vectors display tropism for a wide range of human tissues, avidly infect primary cells and have a good safety profile. In the present study, we therefore used a next‐generation sequencing (NGS) barcoded AAV screening method to assess transduction capability of a panel of 36 AAVs in primary cell lines representing high‐grade glioma (HGG) brain tumours including glioblastoma (GBM) and diffuse intrinsic pontine glioma (DIPG)/diffuse midline glioma (DMG). As proof of principle, we created a reporter construct to analyse activity of the transcriptional co‐activators yes‐associated protein (YAP) and transcriptional co‐activator with PDZ‐binding motif (TAZ). Transcriptional activation was monitored by promoter‐driven expression of the Timer fluorescent tag, a protein that fluoresces green immediately after transcription and transitions to red fluorescence over time. As expected, attempts to express the reporter in primary HGG cells from plasmid expression vectors were unsuccessful. Using the top candidate from the AAV screen, we demonstrate successful AAV‐mediated transduction of HGG cells with the YAP/TAZ dynamic activity reporter. In summary, the NGS‐screening approach facilitated screening of many potential AAVs, identifying vectors that can be used to study the biology of primary HGG cells.